Interference of peptone and tyrosine with the lignin peroxidase assay. - ten Have, R (1997)
The N-unregulated white rot fungus Bjerkandera sp. strain BOS55 was cultured in 1 liter of peptone-yeast extract medium to produce lignin peroxidase (LiP). During the LiP assay, the oxidation of veratryl alcohol to veratraldehyde was inhibited due to tyrosine present in the peptone and the yeast extract.